2005
DOI: 10.1002/anie.200461583
|View full text |Cite
|
Sign up to set email alerts
|

The Origin of One‐Bond C–H Coupling Constants in OCH Fragments: Not Primarily nO→${{\rm \sigma} {{\ast \hfill \atop {\rm CH}\hfill}}}$ Delocalization

Abstract: Conforming couples: Coupling constants 1JCH and CH bond lengths were calculated for various conformations of tetrahydropyran, ethyl methyl ether, and dimethyl ether. The dependence of 1JCH on the H‐C‐O‐C dihedral angle does not parallel the nO→${{{\rm \sigma} {{\ast \hfill \atop {\rm {\rm CH}}\hfill}}}}$ delocalization (see picture). Dipolar interactions that affect electron densities are proposed to be responsible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
27
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 12 publications
3
27
0
Order By: Relevance
“…s à CÀH interaction is expected involving oxygen lone-pair donation into the C-H antibonding orbital. 7 Although the magnitude of the 1 J CHax coupling constant is smaller than 1 J CHeq as expected, it was concluded that this was not dictated by hyperconjugation. Instead, natural bond orbital (NBO) theory analysis for a variety of different conformers and analogs of 3 highlighted a correlation between the molecular dipole moment and 1 J CH .…”
mentioning
confidence: 74%
“…s à CÀH interaction is expected involving oxygen lone-pair donation into the C-H antibonding orbital. 7 Although the magnitude of the 1 J CHax coupling constant is smaller than 1 J CHeq as expected, it was concluded that this was not dictated by hyperconjugation. Instead, natural bond orbital (NBO) theory analysis for a variety of different conformers and analogs of 3 highlighted a correlation between the molecular dipole moment and 1 J CH .…”
mentioning
confidence: 74%
“…Yet, an alternative explanation based on the dipolar interaction [35,36] cannot be irrevocably ruled out at least unless the behavior of 1 J CH as a function of the HCSO dihedral angle is not monitored in the whole range from 0 to 180 • . The investigated silathiane S-oxides probe it only of 60 • for SO eq and of 160 • for SO ax and do not allow going to small angles that would make it possible to distinguish between the hyperconjugation effects and dipolar interactions.…”
Section: Methodsmentioning
confidence: 95%
“…However, recently the concept of the n X → σ * (C−H) hyperconjugation was rejected as primarily responsible for 1 J CH (the Perlin effect) [35] and 1 J CC coupling constants [36] at least, in ethers. Yet, as the authors specially emphasized [35,36], their conclusion is not necessarily general and, therefore, depending on the energy gap between the interacting orbitals and their ability to delocalization, hyperconjugation effects might play an important and even the seminal role in determining the values of coupling constants.…”
Section: Methodsmentioning
confidence: 98%
“…Moreover, they reveal the fundamental role played by the axial substituent stereoelectronic effect in weakening an antiperiplanar C-H bond, which, to the best of our knowledge, has never been observed before. Of course, we are fully aware that the structure and interactions present in 6a and 6f are, by far, more complex than models reported in the literature, and that both the origin [33] and the magnitude of the 1 J C-H values can be affected by torsional effects of the substituents. [34] However, the 1 J C-H values completely agree with considerations we used to explain the regiospecificity observed in the elimination reactions of talo 4-O-imidazylates.…”
mentioning
confidence: 95%
“…Recent results from Cuevas and co-workers indicate that any stereoelectronic interaction weakening an axial C-H bond is manifested in a smaller 1 J C-Hax value, relative to that of 1 J C-Heq . [33] Starting from these considerations, we compared ( Table 2) the 1 J C-H values of a strictly similar couple of talo-and galactopyranosides (6a and 6f), in order to determine if there is spectroscopic evidence of the stereoelectronic effect exerted by the axial benzyloxy group at C-2 of 6a. As expected, both the axial 1 J C1-H1 and 1 J C3-H3 values of the talo compound 6a were smaller than the analogous coupling constants in the galactopyranoside 6f ( Table 2).…”
mentioning
confidence: 99%